ANALISIS FUNGSI BIAYA HAMPERS COKLAT UNTUK MENERAPKAN SISTEM PENGENDALIAN BIAYA YANG EFEKTIF - Mahira, Sarah; Novita Sari, Putri; Yustina, Kristin; Kartika, Ika; Wiwiek Nurkomala Dewi (Jurnal Witana, 2025)
Cost control in business operations is a vital process. Systematic calculations and capital management are that things need to be considered. Analysis of production and capital costs requires mathematical calculations that are implemented, thorugh cost function analysis. This study aimed at analyizing the cost function of chocolate hampers to effective cost control system is implemented. Systematic of mathematical calculation in planned loading analysis wihich concist of fixed cost, variable cost, and total cost which result in achieving production targets which reduce unnecessary cost. This studys method is quantitative descriptive which concist of two type of data, namely, primary and secondary data. Studys was carried out in the gift business sector. The objecet of studys is Chloe’s chocolate store. Data collection caried out through interviews, and observation. Studyes asked questions regarding production cost and level quantity product units.The informant interviewed was the owner of the hampers store with a total of 1 informant. Data peresentation was carried numbers, tables, and graphes which explained mathematically. The data showed bained of implications between the mathematical process of function analysis and the cost control system at the Chloe’s chocolate store. The level of sales is in line with the numbers of production unit produced. The results of the studys conducted by studys show the cost function alaysis can be applied to an effective production and control system.